Relationship between Pilates practice time and the electromyographic response of pelvic floor muscles in climacteric women: An observational study (Research, Society and Development, 2021)
Ojective: To analyze the relationship between practice time in the Pilates method and the electromyographic response of the pelvic floor muscles (PFM) in climacteric women. Design: An observational study. Participants: Twenty-eight (28) climacteric women with a mean age of 53.97 (± 6.11) years and a minimum period of 6 months of practicing the Pilates Method. Main Outcome Measures: An evaluation sheet containing sociodemographic, obstetric and gynecological data. Electromyographic capture of PFM by surface electromyography (Miotool Uro 200, Miotec®, Brazil). Results: The results showed that the electromyographic data (base tone, maximum voluntary contraction, sustained contraction) did not show statistical correlation between the data (r > -0.057; p > 0.63). Conclusions: The Pilates Method does not seem to influence the electromyographic response of PFM. The findings suggest that this cannot be considered a specific activity for training the pelvic floor muscles.